2021
DOI: 10.3390/molecules26206294
|View full text |Cite
|
Sign up to set email alerts
|

Lipid A-Mediated Bacterial–Host Chemical Ecology: Synthetic Research of Bacterial Lipid As and Their Development as Adjuvants

Abstract: Gram-negative bacterial cell surface component lipopolysaccharide (LPS) and its active principle, lipid A, exhibit immunostimulatory effects and have the potential to act as adjuvants. However, canonical LPS acts as an endotoxin by hyperstimulating the immune response. Therefore, LPS and lipid A must be structurally modified to minimize their toxic effects while maintaining their adjuvant effect for application as vaccine adjuvants. In the field of chemical ecology research, various biological phenomena occurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 85 publications
1
10
0
Order By: Relevance
“…Previous studies have shown that the chain length and distribution pattern of fatty acids and the number of phosphate groups affect their activities. [1,3,10] Compared to the structure of E. coli lipid A, hexa-ApLA (1) possesses i) a GlcA residue in place of the reducing end phosphate group, ii) a Man residue instead of the non-reducing end phosphate group, and iii) a relatively longer fatty acid chain. Our results suggest that the carboxylate in the GlcA residue of hexa-ApLA (1) can play an alternative role to the reducing end-phosphate group.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that the chain length and distribution pattern of fatty acids and the number of phosphate groups affect their activities. [1,3,10] Compared to the structure of E. coli lipid A, hexa-ApLA (1) possesses i) a GlcA residue in place of the reducing end phosphate group, ii) a Man residue instead of the non-reducing end phosphate group, and iii) a relatively longer fatty acid chain. Our results suggest that the carboxylate in the GlcA residue of hexa-ApLA (1) can play an alternative role to the reducing end-phosphate group.…”
Section: Methodsmentioning
confidence: 99%
“…Lipopolysaccharide (LPS) is a cell surface component of Gram-negative bacteria that activates innate immunity to induce the release of inflammatory cytokines, nitric oxide, and reactive oxygen species. [1][2][3] LPS generally consists of a polysaccharide moiety, termed the O-antigen, a core oligosaccharide region, and the glycolipid lipid A, located at the terminal of LPS. [1][2][3] The lipid A moiety is widely known as the active principle for the immunostimulatory effects of LPS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Therefore, the deletion of core oligosaccharides, O-antigen, colanic acid, and ECA gene clusters in E. coli could avoid the accumulation of precursors and metabolic intermediates of these polysaccharides and regulate the proportion of intracellular carbon and nitrogen sources 10,11 (Figure 1). Lipid A is the bioactive center of LPS 12 ; it can be recognized by the pathogen recognition receptor toll-like receptor 4 (TLR4) on immune cells in the host, leading to the release of cytokines, 13 and generation of strong Th1 responses. 14 Monophosphoryl lipid A (MPL) is synthesized by Salmonella minnesota R595, and its toxicity level is only 0.1% that of the typical lipid A, but it has considerable immunostimulatory activity.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, LPS/lipid A structures that are ineffective in activating the TLR4-mediated signalling while keeping the capability to bind the receptor and to prevent the binding of agonistic LPS are defined as antagonists [10,11]. In this frame, the search for novel lipid A structures [10][11][12][13][14][15] that might possess any immunomodulatory activity towards TLR4/MD-2-dependent signalling is of high relevance for researchers of both the biomedical and pharmacological field who are attracted by the possibility to finely tune the immune response and, hence the inflammatory process(es). Consequently, due to the intrinsic nature of living and thriving in extreme habitats, deep-sea bacteria are evaluated as harmless for humans, therefore they can be considered as a "gold mine" for the discovery of new LPS and lipid A molecules to be isolated and analysed for the realization of new generation immune-therapeutics inspired by a natural source.…”
Section: Introductionmentioning
confidence: 99%